2018
DOI: 10.1136/bmjgast-2018-000208
|View full text |Cite
|
Sign up to set email alerts
|

Putative biomarkers of vedolizumab resistance and underlying inflammatory pathways involved in IBD

Abstract: ObjectivesCharacterise the circulating inflammatory cytokine pattern among patients failing consecutive anti-tumour necrosis factor (anti-TNF) and anti-integrin treatments to identify predictors of response.MethodsA retrospective single-centre cohort study of 28 patients with inflammatory bowel disease (IBD) receiving anti-integrin therapy (vedolizumab) subsequent to the failure of anti-TNF treatment was conducted. Blood samples were obtained immediately prior to initiation of vedolizumab therapy, and the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…Other studies have examined whether other cytokines and cytokine receptors could be useful markers of anti-TNF responses [[96], [97], [98]]. West and colleagues demonstrated that the expression of OSM can be used to predict response to anti-TNF therapy [96].…”
Section: Predicting Anti-tnf Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have examined whether other cytokines and cytokine receptors could be useful markers of anti-TNF responses [[96], [97], [98]]. West and colleagues demonstrated that the expression of OSM can be used to predict response to anti-TNF therapy [96].…”
Section: Predicting Anti-tnf Responsesmentioning
confidence: 99%
“…Interestingly, α 4 β 7 expression on CD4 + T cells and Natural Killer (NK) cells prior to treatment was found to be higher in responders than non-responders [110]. A separate study of 11 CD and 17 UC patients found that vedolizumab non-responders had higher baseline levels of circulating IL-6 [97], and that CD40 Ligand (100% specificity/sensitivity) and osteocalcin (100% specificity, 85% sensitivity) could predict response in CD or UC patients, respectively. These observations are encouraging, but the cohort size was small in both of these studies and further validation is required.…”
Section: Predicting Response To Non-anti-tnf Biologicsmentioning
confidence: 99%
“…Previous studies have primarily focused on linking genetic polymorphisms associated with IBD to the response to biological treatment, however, associations are vague and suggest that other omics profiles are also implicated 17 18. Recent findings indicate that mucosal inflammatory patterns and serum cytokine profiles differ between responders and non-responders to biological treatment 19–22. Furthermore, interactions between host and gut microbiota play a pivotal role in IBD pathogenesis and should be taken into consideration when predicting treatment response 23 24.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, vedolizumab-specific biomarkers are even more limited, with studies focusing only on prediction of clinical response. 8,9 As targets in IBD are evolving from clinical to endoscopic remission, 10 biomarker development should focus on the prediction of endoscopic remission.…”
mentioning
confidence: 99%